2005
DOI: 10.1074/jbc.m410660200
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-selective Mutants of Apoptosis-inducing Ligand 2/Tumor Necrosis Factor-related Apoptosis-inducing Ligand Reveal a Greater Contribution of Death Receptor (DR) 5 than DR4 to Apoptosis Signaling

Abstract: Apoptosis-inducing ligand 2 (Apo2L), also called tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), triggers programmed cell death in various types of cancer cells but not in most normal cells. Apo2L/TRAIL is a homotrimeric protein that interacts with five receptors: death receptor 4 (DR4) and DR5 mediate apoptosis activation, whereas decoy receptor 1 (DcR1), DcR2, and osteoprotegerin counteract this function. Many cancer cell lines express both DR4 and DR5, and each of these receptors can initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
212
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(230 citation statements)
references
References 28 publications
15
212
2
1
Order By: Relevance
“…Characterization of the mechanisms underlying this enhancement revealed two novel findings of dipyridamole treatment: (1) upregulation of TRAIL DRs, and (2) downregulation of survivin, which are well-known regulators of TRAIL-triggered apoptotic signals (Azuhata et al, 2006;Carlo-Stella et al, 2007). We have also shown that DR5 contributed preferentially toward dipyridamole-induced TRAIL sensitization, corroborating the findings reported previously (Kelley et al, 2005). …”
Section: Discussionsupporting
confidence: 93%
“…Characterization of the mechanisms underlying this enhancement revealed two novel findings of dipyridamole treatment: (1) upregulation of TRAIL DRs, and (2) downregulation of survivin, which are well-known regulators of TRAIL-triggered apoptotic signals (Azuhata et al, 2006;Carlo-Stella et al, 2007). We have also shown that DR5 contributed preferentially toward dipyridamole-induced TRAIL sensitization, corroborating the findings reported previously (Kelley et al, 2005). …”
Section: Discussionsupporting
confidence: 93%
“…1, 3), suggesting that other factors regulate the sensitivity at the downstream signaling of the receptors. However, it seems that some leukemia cells undergo apoptotic cell death through signaling by either pro-apoptotic DR4 or DR5, but not both, as has been found for various solid tumors [25,26]. The substantial sensitivity of HL-60 (AML) and U937 (monoblastic leukemia) cells to TRAIL-mediated cytotoxicity, but not to AY4, suggests that DR5 is the main receptor that transduces apoptotic signaling in the leukemia cells.…”
Section: Discussionmentioning
confidence: 91%
“…The receptor-specific agonistic mAb studies demonstrated that, while various solid tumors were more sensitive to DR5-mediated apoptosis than DR4-induced apoptosis [25,26], primary CLL cells underwent apoptotic cell death almost exclusively through DR4, not DR5 [23,24,27]. However, there have been limited studies of how DR4-or DR5-mediated signaling alone or in combination with chemotherapeutic agents can contribute to apoptosis for other leukemia cells, such as ALL, AML, and CML cells.…”
Section: Introductionmentioning
confidence: 99%
“…The differential effect of noncrosslinked hTRAIL on KB and L929 cells can be explained by earlier findings demonstrating that TRAILR2 is much more better activated by secondary cross-linked trimers of soluble TRAIL than by non-crosslinked molecules, whereas TRAILR1 is stimulated with the same efficiency by crosslinked and non-crosslinked TRAIL. 5,13,14 Thus, in KB cells that express TRAILR1 and TRAILR2, non-crosslinked TRAIL trimers already significantly induce cell death via the TRAILR1, whereas TRAILR1-mediated cell death is not relevant in the murine L929 cell line, because in mice only a homolog of human TRAILR2 exists. 15,16 In fact, in human Jurkat cells, which express only TRAILR2, noncrosslinked Flag-hTRAIL(95-291) is also practically inactive (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%